1992
DOI: 10.1128/aac.36.5.913
|View full text |Cite
|
Sign up to set email alerts
|

Evidence that tetracycline analogs whose primary target is not the bacterial ribosome cause lysis of Escherichia coli

Abstract: The modes of action of atypical tetracyclines that do not directly inhibit bacterial protein synthesis were investigated. The analogs tested, chelocardin, anhydrotetracycline, 6-thiatetracycline, anhydrochlortetracycline, and 4-epi-anhydrochlortetracycline, were bactericidal and caused the lysis of Escherichia coli accompanied by the release of the cytoplasmic enzyme 1-galactosidase into the supernatant. Examination by electron microscopy demonstrated that cells exposed to these analogs underwent marked morpho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
69
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(70 citation statements)
references
References 16 publications
1
69
0
Order By: Relevance
“…Nevertheless, it has now been established that the thiatetracyclines and a number of other tetracycline analogs, referred to collectively as atypical tetracyclines (43,44), exhibit a different structure-activity relationship from the majority of tetracyclines. These molecules, which also include the anhydrotetracyclines, 4-epi-anhydrotetracyclines, and chelocardin, appear to directly perturb the bacterial cytoplasmic membrane, leading to a bactericidal response (43,198,199). This contrasts with the typical tetracyclines, which interact with the ribosome to inhibit bacterial protein synthesis and display a reversible bacteriostatic effect.…”
Section: Structure-activity Relationshipsmentioning
confidence: 81%
See 1 more Smart Citation
“…Nevertheless, it has now been established that the thiatetracyclines and a number of other tetracycline analogs, referred to collectively as atypical tetracyclines (43,44), exhibit a different structure-activity relationship from the majority of tetracyclines. These molecules, which also include the anhydrotetracyclines, 4-epi-anhydrotetracyclines, and chelocardin, appear to directly perturb the bacterial cytoplasmic membrane, leading to a bactericidal response (43,198,199). This contrasts with the typical tetracyclines, which interact with the ribosome to inhibit bacterial protein synthesis and display a reversible bacteriostatic effect.…”
Section: Structure-activity Relationshipsmentioning
confidence: 81%
“…Agents Chemother., abstr. 679, p. 199,1990). On further examination, the phenotype was not stably transferred and was most probably an artifact of the growth conditions (Jones et al, 30th ICAAC).…”
Section: Incidence Of Tetracycline Resistancementioning
confidence: 99%
“…The overall lack of literature concerning hormetic response in bacteria does not allow to speculate too much about the underlying mechanisms; experiments performed with the typical ribosome-inhibiting Tetracyclines, at doses by far higher than those causing the response we described, demonstrated that no morphological changes occur in E. coli cells (Oliva et al 1992). The mechanism underlying this kind of hormetic response, that is a time-limited enhancing of the number of bacterial cells, recalls an r-strategy reaction -and, indeed, E. coli is an r-strategist species -global regulation systems could therefore be activated in the presence of many, even unrelated kind of stresses including these very low antibiotic doses.…”
Section: Discussionmentioning
confidence: 99%
“…Chlorotetracycline is thought to interfere with bacterial membranes' electrochemical gradient, which led to the stimulation of autolytic enzyme activity and cellular lysis. The filamentation induced by tetracycline before lysis could have been caused by a direct inhibitory action on DNA synthesis, as explained by Oliva et al (1992).…”
Section: Discussionmentioning
confidence: 99%